The Patriarchy Trap: The Role of Internalized Misogyny in Predicting Communicative Undermining Among Women - Wahyudi, Anatasia; Kartikawati, Dwi (SERUNAI, 2025)
The global pursuit of gender equality is fundamentally challenged by a paradoxical social friction known as Communicative Undermining among Women (Y), where women engage in critical and diminishing behaviors toward their peers. This study investigates the psychological root cause of this phenomenon, focusing on Internalized Misogyny (X), defined as the unconscious adoption of negative gender stereotypes derived from a patriarchal environment. Grounded in Social Cognitive Theory (SCT), the research aims to statistically quantify how these internalized beliefs drive aggressive interpersonal communication and subsequently erode women’s collective self-efficacy. Following the quantitative framework proposed by Creswell (2016), a systematic four-stage procedure was employed: a pilot study (N=30) for instrument validation, main data collection via Google Forms from 102 women (aged 20-40) in DKI Jakarta, prerequisite assumption testing, and simple linear regression analysis using SPSS. The findings reveal that Internalized Misogyny has a positive and significant influence on Communicative Undermining, with a remarkably high predictive power (R2 = 70.1%, p < 0.001). This suggests that the internalization of detrimental gender stereotypes accounts for the majority of the variance in undermining behaviors. The study concludes that the "Patriarchy Trap" functions by redirecting systemic oppression into lateral conflict, thereby diminishing the self-efficacy of women targets. These results mandate a shift in deconstruction and gender-critical literacy over surface-level conflict resolution to restore genuine women solidarity and collective resilience.